2019
DOI: 10.1111/andr.12704
|View full text |Cite
|
Sign up to set email alerts
|

Sequence analysis of 37 candidate genes for male infertility: challenges in variant assessment and validating genes

Abstract: Background The routine genetic analysis for diagnosing male infertility has not changed over the last twenty years, and currently available tests can only determine the etiology of 4% of unselected infertile patients. Thus, to create new diagnostic assays, we must better understand the molecular and genetic mechanisms of male infertility. Although next‐generation sequencing allows for simultaneous analysis of hundreds of genes and the discovery of novel candidates related to male infertility, so far only a few… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 46 publications
0
29
0
Order By: Relevance
“…We identified two homozygous LoF variants in TEX14 in two unrelated patients affected by incomplete spermatogonial arrest. Previously reported TEX14 variants were associated with testis histology ranging from SCO to complete SCA 20 22 . With the discovery of the two new TEX14 variant carriers, this gene can now be upgraded to strong clinical evidence.…”
Section: Discussionmentioning
confidence: 95%
“…We identified two homozygous LoF variants in TEX14 in two unrelated patients affected by incomplete spermatogonial arrest. Previously reported TEX14 variants were associated with testis histology ranging from SCO to complete SCA 20 22 . With the discovery of the two new TEX14 variant carriers, this gene can now be upgraded to strong clinical evidence.…”
Section: Discussionmentioning
confidence: 95%
“…One year later, Tewes and colleagues [110] analysed the DMRT1 sequence in 131 individuals diagnosed with NOA and 215 normozoospermic controls, reporting two cases of NOA (one of them with SCO) that showed heterozygosity for a putative pathogenic transition mutation in the third exon of the gene. The DMRT1 mutation observed in the SCO patient was detected in another NOA individual from Brazil (from a total of 16 azoospermic patients analysed) in a recent study [111].…”
Section: Dmrt1mentioning
confidence: 79%
“…Colombo and colleagues [127] performed exome sequencing in two infertile siblings affected by NOA, identifying another nonsense mutation and a single nucleotide deletion that led to premature stop codons in the TEX15 locus. Finally, the recent sequencing study of 16 Brazilian patients affected by NOA by Araujo et al [111] also reported novel rare variants in both TEX14 and TEX15.…”
Section: Tex14 and Tex15mentioning
confidence: 86%
“…The ancestral mammalian Y chromosome lost a vast number of genes, which moved to autosomes during evolution (Hughes, Skaletsky, Koutseva, Pyntikova, & Page, 2015;Mendez, Poznik, Castellano, & Bustamante, 2016). Numerous studies have shown that several genes expressed in the testis are associated with fertility potential (Araujo et al, 2019;van der Bijl et al, 2019). The expression of inserted gene copies was reported to be increased in the testis, thus suggesting a possible function in spermatogenesis (Ropke et al, 2013).…”
Section: Autosomal Gene Mutationsmentioning
confidence: 99%